Relative comparison of chronic kidney disease-mineral and bone disorder rat models - Zhang, Xiaoqiong; Li, Ting; Wang, Lijuan; Li, Yanhui; Ruan, Taoren; Guo, Xiaohong; Wang, Qin; Meng, Xianli (Frontiers in Physiology, 2023)
Objective:To establish a suitable animal model of chronic kidney disease-mineral and bone disorder (CKD-MBD) by comparatively studying the CKD-MBD rat models induced by 5/6Nx, AN and UUO with low-calcium and high-phosphorus diet respectively. Methods: Sprague-Dawley rats were randomized into four groups: control group, 5/6 nephrectomy group (5/6Nx), adriamycin nephropathy group (AN) and unilateral ureteral obstruction group (UUO). Serum biochemical indexes were detected to evaluate the renal function, the mineral and bone metabolism, the severity of CKD-MBD and the status of bone transformation. Hematoxylin-eosin staining (HE) and Masson’s trichrome (Masson) staining were used to observe the histopathology of kidney and femur. Goldner trichrome (Goldner) and Tartrate-resistant acid phosphatase (Trap) staining were utilized to observe the bone mineralization and the osteoclasts in femur, respectively. Micro CT image was applied to study the structure of femur. The expressions of Osterix and Cathpesin K in femur were detected by immunohistochemical (IHC) to confirm the status of bone. Results: The levels of Scr and BUN in the 5/6Nx and the AN rats were significant higher than that in the control rats, accompanied with extremely disorder in the levels of Ca, Pi, i-PTH, OC and CTX-1; UUO rats exhibited slight and indistinctive variation in the levels of Scr, BUN, Ca, Pi, i-PTH, OC and CTX-1 in serum. The histopathology of kidney showed that UUO rats suffered the serious fibrosis and 5/6Nx rats underwent the severe focal calcification. The histopathology of femur displayed that AN rats had the minimal bone mineralization and 5/6Nx rats had the hyperactive osteoclasts. Micro CT revealed that AN rats had the most serious bone destruction and 5/6Nx rats had the slightest bone loss among the three models. The expression of Cathpesin K in femur were significantly increased in all models, while the expressions of Osterix in femur was only significantly increased in 5/6Nx model. Conclusions. The 5/6Nx, AN and UUO with low-calcium and high-phosphorus diet can induce CKD-MBD rat model successfully. The 5/6Nx is a suitable model utilized in studying the prevention and treatment of CKD-MBD because it is easy to monitor and observe the progression of hyperactive bone transformation in CKD-MBD.